Evolutionary biology concepts, biodiversity, macroevolution and genome evolution - Pontarotti, Pierre; SpringerLink (Online service). (Heidelberg New York Springer-Verlag Berlin Heidelberg, 2011)
The annual Evolutionary Biology Meetings in Marseilles serve to gather leading scientists, promote the exchange of ideas and encourage the formation of international collaborations. This book contains the most essential contributions presented at the 14th Evolutionary Biology Meeting, which took place in September 2010. It comprises 19 chapters organized according to the following categories: Evolutionary Biology Concepts; Biodiversity and Evolution; Macroevolution Genome; Evolution Offering an up-to-date overview of recent results in the field of evolutionary biology.
Electronic reproduction.
Keywords: Evolution (Biology).; Electronic books